Creating Philanthropic Capital Markets - Lucy Bernholz, (jhony wiley & sony.isc, 2003)
This book draws on experiences and insights gained from more than 12 years of work in philanthropy. I am indebted to all of my colleagues, clients, advisors, and peers for the questions they ask, the innovations they have developed, and the work they do every day. My job consists of working directly with clients—foundations, individuals, philanthropic associations, and other grant makers—and then stepping back from those practical engagements to ask big questions about the philanthropic industry. I have learned from each and every client, and their collective wisdom infuses this book, although any faults in interpretation are solely mine. I wish to thank several people for their good-natured professional and intellectual guidance and critique. Jack Chin, Lindy Flynn, Lori Jones, Gabriel Kasper, Stephanie Fuerstner Gillis, Susan Grand, Kendall Guthrie, Amy Luckey, Kaitlin McGaw, Adelaide Nalley, and Alan Preston inform and challenge my thinking on a daily basis. Deborah Alvarez Rodriguez, Rachel Newton Bellow, Daniel Ben-Horin, Laura Breeden, Paul Brest, Diana Campoamor, Jim Canales, Emmett Carson, Winnie Chu, Cristina Cuevas, Alexa Culwell, Katherine Fulton, Diane Frankel, David Kennedy, Elan Garonzik, Nancy Glaze, Crystal Hayling, Peter Hero, Barbara Kibbe, Joe Lumarda, Robin Larson, Rochelle Lefkowitz, Lance Linares, Milbrey McGlaughlin, Julie Rogers, Peggy Saika, Bruce Sievers, Ralph Smith, Sterling Spiern, Kirke Wilson, Tim Wilmot, Jim Watson, Sylvia Yee, and board members of the David L. Klein Jr. Foundation have all pushed me in some important way over the years, and I am a better thinker because of it. Thank you.